2004
DOI: 10.1063/1.1794376
|View full text |Cite
|
Sign up to set email alerts
|

Modulation derived satellite peaks in x-ray reciprocal mapping on bismuth cuprate superconductor film

Abstract: X-ray reciprocal space mapping (XRSM) was employed to investigate epitaxial Bi2Sr2Ca1Cu2Ox(Bi-2212) film. Ordinal cross section XRSM (ω-2θ) and plan view XRSM (ω-ψ) clearly indicated asymmetric intensity distribution of four satellite peaks caused by supercell structure of Bi-2212 film. Modulation vector estimated by XRSM was q=0.2b*+0.9c*. The XRSM image simulated by sawtooth wave vector showed good agreement with asymmetric satellite peaks observed on epitaxial film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…[15]. The SC model modulated by the sawtooth wave (sawtooth model) showed lower satellites around Bi-2212 ð0 0 2 0Þ, which is in good agreement with experimental results on epitaxial film [12]. For Bi-2212 ð0 0 1 2Þ reflection, XRSM showed upper satellites as shown in Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…[15]. The SC model modulated by the sawtooth wave (sawtooth model) showed lower satellites around Bi-2212 ð0 0 2 0Þ, which is in good agreement with experimental results on epitaxial film [12]. For Bi-2212 ð0 0 1 2Þ reflection, XRSM showed upper satellites as shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…We have previously reported that satellite peaks caused by SC structure were observed in Bi 2 Sr 2 Ca 1 Cu 2 O X (Bi-2212) epitaxial film using X-ray reciprocal space mapping (XRSM) [12]. Instead of symmetric satellite peaks observed on single crystal, asymmetric satellite peaks were observed in Bi 2 Sr 2 Ca 1 Cu 2 O X (Bi-2212) epitaxial film.…”
Section: Introductionmentioning
confidence: 94%
“…Relatively thick films were prepared in the same manner, and investigated by XRD methods. The details in experimental can be found elsewhere [10][11][12]. Contrary to the multilayered structure, thick Bi-2212 films were prepared to investigate the effect of strain in Bi-2212 film.…”
Section: Methodsmentioning
confidence: 99%
“…Reciprocal space of such structure shows satellite peaks around the main reflection generated by unit cell structure. While symmetric fourfold satellites in intensity and distribution have been observed on single crystal [1][2][3][4][5][6][7][8][9], asymmetric satellite peaks were observed by X-ray reciprocal space mapping (XRSM) on epitaxial thin film [10][11][12].…”
Section: Introductionmentioning
confidence: 97%
“…The symmetric peaks observed on bulk samples can be generated by modulation vector as a sinus function modulating unit cells through its crystal, and the asymmetric peaks are described by triangle function [11]. Another XRSM shows the SC modulations exist along both a and b axes.…”
Section: Introductionmentioning
confidence: 99%